The effect of peer relationships on college students’ behavioral intentions to be physically active: The chain-mediated role of social support and exercise self-efficacy - Xielin Zhou; Mu Zhang; Lu Chen; Bo Li; Jiao Xu (PLoS ONE, 2025)
Purpose Physical activity behavioral intentions have a positive impact on individuals’ physical and mental health, social adjustment, and academic work. This study explored the effects of peer relationships on college students’ behavioral intentions for physical activity and analyzed the mediating role of social support and exercise self-efficacy. Methods The Peer Relationship Inventory, the Physical Activity Rating Scale-Intentions to Physical Activity Behavior subscale, the Social Support Scale, and the Exercise Self-Efficacy Scale were used to psychometrically measure 514 college students (age = 19.00 ± 1.27) from June 3, 2024, to June 7, 2024, and the Bootstrap method was used to mediate the relationship between social support and exercise self-efficacy. Results (1) Peer relationships, social support, exercise self-efficacy and intention to engage in physical activity behaviors were positively correlated (all p < 0.01); (2) gender differences in exercise self-efficacy and intention to engage in physical activity behaviors existed (p < 0.001), and male students scored higher than female students (M ± SD: 3.18 ± 0.55 > 2.98 ± 0.59; 3.23 ± 0.62 > 2.95 ± 0.61); (3) the mediating effect size of social support (peer relationship→social support→behavioral intention to exercise) was 0.078, which accounted for 8.83% of the total effect, and that of exercise self-efficacy (peer relationship→exercise self-efficacy→behavioral intention to exercise) was 0.314, which accounted for 35.56% of the total effect, the chained mediation effect of social support and exercise The chain mediation effect size of self-efficacy (peer relationship→social support→exercise self-efficacy→behavioral intention to exercise) was 0.057, accounting for 6.46% of the total effect, and none of the confidence intervals contained 0. Conclusions (1) College students’ peer relationships can significantly and positively predict behavioral intention to exercise; (2) college students’ peer relationships can have a simple influence on the behavioral intention to exercise through social support and exercise self-efficacy, respectively; (3) College student peer relationships can also influence intention to engage in physical activity through social support and exercise self-efficacy in a chained manner.